REASONS WHY PEOPLE TURN TO VEGETARIAN DIET - Raluca Andreea, Ion (Economics of Agriculture, 2007)
The study is trying to identify the reasons why people turn to vegetarian diet. In order to research this topic, it is done an international literature review on the topic of vegetarianism, considering both pros and cons attitudes and beliefs. Even there are lot of pro vegetarian diet, however, there are studies showing that strict vegetarianism implies health risks and economical inefficiency. The research indicates that vegetarians have varied motivations including health, ethical, economic, environmental, religious, cultural and social concerns. This conclusion has implication for educating consumers to eat healthier, and for food producers and sellers to adapt their strategies to the new tendencies in food consumption.